Architectural design of IoT-cloud computing integration platform - Adhitya Bhawiyuga; Dany Primanita Kartikasari; Kasyful Amron; Ocki Bagus Pratama; Moch. Wildan Habibi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
An integration between the Internet of Things (IoT) and cloud computing can potentially leverage the utilization of both sides. As the IoT based system is mostly composed by the interconnection of pervasive and constrained devices, it can take a benefit of virtually unlimited resources of cloud entity i.e storage and computation services to store and process its sensed data. On the other hand, the cloud computing system may get benefit from IoT by broadening its reach to real world environment applications. In order to incarnate this idea, a cloud software platform is needed to provide an integration layer between the IoT and cloud computing taking into account the heterogenity of network communication protocols as well as the security and data management issues. In this study, an architectural design of IoT-cloud platform for IoT and cloud computing integration is presented. The proposed software platform can be decomposed into five main components namely cloud-to-device interface, authentication, data management, and cloud-to-user interface component. In general, the cloud-to-device interface acts as a data transmission endpoint between the whole cloud platform system and its IoT devices counterpart. Before a session of data transmission established, the communication interface contact the authentication component to make sure that the corresponding IoT device is legitimate before it allowed for sending the sensor data to cloud environment. Notice that a valid IoT device can be registered to the cloud system through web console component. The received sensor data are then collected in data storage component. Any stored data can be further analyzed by data processing component. User or any developed applications can then retrieve collected data, either raw or processed data, through API data access and web console.